Baseline NT‐proBNP Accurately Predicts Symptom Response to Transcatheter Aortic Valve Implantation - Christopher J. Allen; Jubin Joseph; Tiffany Patterson; Matthew Hammond‐Haley; Hannah Z. R. McConkey; Bernard D. Prendergast; Michael Marber; Simon R. Redwood (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Up to 30% of patients undergoing transcatheter aortic valve implantation (TAVI) experience minimal symptomatic benefit or die within 1 year, indicating an urgent need for enhanced patient selection. Previous analyses of baseline NT‐proBNP (N‐terminal pro‐brain natriuretic peptide) and TAVI outcomes have assumed a linear relationship, yielding conflicting results. We reexamined the relationship between baseline NT‐proBNP and symptomatic improvement after TAVI. Methods and Results Symptom status, clinical and echocardiographic data, and baseline NT‐proBNP were reviewed from 144 consecutive patients undergoing TAVI for severe symptomatic aortic stenosis. The primary end point was change in New York Heart Association functional class at 1 year. There was a nonlinear, inverted‐U relationship between log‐baseline NT‐proBNP and post‐TAVI change in NYHA class (R2=0.4559). NT‐proBNP thresholds of <800 and >10 000 ng/L accurately predicted no symptomatic improvement at 1 year (sensitivity 88%, specificity 83%, positive predictive value 72%, negative predictive value 93%). In adjusted analyses, baseline NT‐proBNP outside this “sweet‐spot” range was the only factor independently associated with poor functional outcome (high: NT‐proBNP >10 000 ng/L, odds ratio [OR], 65; 95% CI, 6–664; low: NT‐proBNP <800 ng/L, OR, 73; 95% CI, 7–738). Conclusions Baseline NT‐proBNP is a useful prognostic marker to predict poor symptom relief after TAVI and may indicate when intervention is likely to be futile. Both low (<800 ng/L) and very high (>10 000 ng/L) levels are strongly associated with poor functional outcome, suggesting an alternative cause for symptoms in the former scenario and an irrevocably diseased left ventricle in the latter. Further evaluation of this relationship is warranted.